The Problem of Rebuilding the State in Iraq After 2003 - Salahaddin Jihad نورهان; Shamal Husain Mustafa شمال (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
Iraq entered a new phase after 2003, as a result of the fall of the political regime through American intervention that brought about change through military force. Thus, the principle propagated in Iraq is the establishment of a state of law and institutions through reliance on a political and democratic system capable of protecting the rights and freedoms of citizens. However, these goals collided with a bitter political and social situation that plunged Iraq into a cycle or cycles of conflict, sometimes bloody, in order to control power and the system. This affected the process of stability and the country entered a cycle of security and political disturbances stemming from sectarian, national and ethnic differences, in addition to the clash of external projects. All of this negatively affected the issue of building an institutional state in Iraq. All of this, there were and still are components to overcome all of these difficulties. This research basically addresses the most important challenges that Iraq faced in order to build the new state. The research also focused on monitoring a group of components that help Iraq overcome these difficulties. Keywords: State reconstruction, sectarianism, political quotas, Iraq after 2003.